Living Jesus : learning the heart of the Gospel - Johnson, Luke Timothy (New York : Harper Collins Publishers, 1946)
"For Johnson, the real Jesus is not simply a historical figure - a dead man whose authentic words and deeds can be approached through historical research and textual analysis. Rather, the real Jesus is the resurrected Lord of Christian faith - a living savior who can be encountered in the world today. Being a Christian means learning this living Jesus by "putting on the mind of Christ" and being transformed in his image." "He demonstrates how Jesus is present in the community of the Christian church - and how the church is instrumental in helping us learn Jesus. For Johnson, the Christian traditions that the church embodies - canon, creed, worship, prayer, veneration of saints, charity toward the powerless - are not dilutions of Jesus' message, but essential components of an authentic Christian spirituality."--Jacket
The truth that is in Jesus. He is the living one ; Learning Jesus through tradition ; He bodies forth whose glory is past change ; The process of learning Jesus ; The living Jesus and the revelatory text ; Paul's witness to Jesus -- Jesus in the Gospels. One person in four portraits. Jesus in Mark's Gospel ; Jesus in Matthew's Gospel -- Jesus in Luke-Acts ; Jesus in John's Gospel -- The continuing mystery.
Includes index.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Resurrection; Jesus Christ -- Biography -- History and criticism; Jesus Christ -- Historicity; Jesus Christ -- History of doctrines -- 20th century; Bible. -- History and criticism